El Niño‐based malaria epidemic warning for Oromia, Ethiopia, from August 2016 to July 2017. Issue 11 (7th October 2016) - Bouma, M. J.; Siraj, A. S.; Rodo, X.; Pascual, M.
Abstract: Objective: Tropical highland malaria intensifies and shifts to higher altitudes during exceptionally warm years. Above‐normal temperatures associated with El Niño during boreal winter months (December–March) may intensify malaria in East African highlands. We assessed the malaria risk for Oromia, the largest region of Ethiopia with around 30 million inhabitants. Methods: Simple linear regression and spatial analyses were used to associate sea surface temperatures (SST) in the Pacific and surface temperatures in Ethiopia with annual malaria risk in Oromia, based on confirmed cases of malaria between 1982 and 2005. Results: A strong association ( R 2 = 0.6, P < 0.001) was identified between malaria and sea surface temperatures in the Pacific, anticipating a 70% increase in malaria risk for the period from August 2016 to July 2017. This forecast was quantitatively supported by elevated land surface temperatures (+1.6 °C) in December 2015. When more station data become available and mean March 2016 temperatures from meteorological stations can be taken into account, a more robust prediction can be issued. Conclusion: An epidemic warning is issued for Oromia, Ethiopia, between August 2016 and July 2017 and may include the pre‐July short malaria season. Similar relationships reported for Madagascar point to an epidemic risk for all East African highlands with around 150 million people. Preparedness for this high risk period would include pre‐emptive intradomestic spraying with insecticides, adequate stocking of antimalarials, and spatial extension of diagnostic capacity and more frequent reporting to enable a rapid public health response when and where required.